The impact of election administration on the legitimacy of hybrid democracy in Nigeria: the case of 2015 general elections - Sakariyau, Rauf Tunde (2018)
Election administration in Nigeria has always been marred with malpractices and violence which threaten democratization process in the country. This makes it imperative in this study to examine the impact of election administration on the legitimacy of hybrid democracy in Nigeria, with the emphasis on the 2015 general elections. Using ‘Structural Functionalism Theory’, ‘Electoral Authoritarianism (EA)’ and ‘Liberal Democratic Theory’ as the main analysis framework, the thesis analyses the effectiveness and weakness of Nigeria’s electoral democracy. The first theoretical segment discusses the functionality of different sub-structures that supported the Independent National Electoral Commission (INEC) in conducting the country’s general elections in 2015, while the second theoretical postulation concentrates on the overall assessment of democratization in Nigeria. This study adopts qualitative method in data collection and analysis. The sources of research data and information were derived from in-depth interview session, focus group discussion, published reports, working papers and relevant scholarly articles and books. By examining and analyzing the nature of Nigeria’s electoral politics, this thesis categorizes the country’s democracy as a ‘Hybrid Democracy,’ combining the values of liberalism and authoritarianism. The findings of this study also indicate that the paradigm shift in the management of the 2015 general elections was anchored on the leadership approach of the Electoral Management Body (EMB) that introduced several innovations and mechanisms which boosted the credibility and integrity of the elections’ exercise. At the same time, the role and impact of other relevant stakeholders which cut across local and international dimensions have also been influential in the conduct of the 2015 general elections. Despite the improvement and success recorded in the 2015 elections, a series of shortcomings ranging from pockets of violence, under-age voting to malfunctioning of the technological gadgets in several polling units remain a major obstacle to electoral democracy in the country. For Nigeria’s electoral democracy to be consolidated, all players who are involved in electioneering process must adhere to electoral guidelines entrenched in the electoral laws and regulations.